Optimasi Ekstraksi Mikroplastik Polystyrene (PS) Dengan Wet Peroxide Oxidation (WPO) - Fatma, Winda Faulina; Dewata, Indang; Mulia, Melindra; Alizar, Alizar (Departemen Kimia FMIPA UNP, 2024)
Plastic pollution is a global problem that is very dangerous if not handled appropriately and systematically. These plastics can enter the environment and will degrade into microplastics due to environmental factors such as light, temperature and humidity. Microplastics are degraded plastics with a size of <5 mm. This microplastic is very dangerous if ingested by living creatures. One of the impacts can cause digestive disorders, cancer and many more. The aim of this research is to obtain an appropriate method for extracting polystyrene microplastics from water samples. The method used is the WPO (wet peroxide oxidation) extraction method. This method uses two solutions, namely Fe(II) 0,05 M as a catalyst to accelerate the oxidation reaction of impurities and H2O2 30% as an OH• producing material which function to oxidize impurities. In the procedure, variations in Fe(II) concentration and heating temperature were carried out. The optimum results obtained were Fe(II) 0,075 M and a heating temperature of 75°C. Apart from that, microplastic characterization was also carried out using FTIR (Fourier Transform InfraRed). Characterization using FTIR shows that the specific functional groups possessed by polystyrene are C-H bending, C=C stretching and C-H stretching at wave numbers 758 cm-1, 1600,97 cm-1 and 2931,90 cm-1, respectively.